2019
DOI: 10.1002/ece3.5205
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of stress imprinting with population‐level differences in two moss species

Abstract: Plants are often repeatedly exposed to stresses during their lives and have a mechanism called stress imprinting that provides “memories” of stresses they experience and increases their ability to cope with later stresses. To test hypotheses that primed bryophytes can preserve their stress imprinting after 6 days of recovery and induce higher levels of osmolytes and ROS‐scavenging activities upon later stress exposure, and there exist population‐level differentiation in their desiccation defenses, we transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…The histone H4 variant TH091 and histone H2A.2.2 (core components of nucleosomes), and the 40S ribosomal protein S15a-1 and 60S ribosomal protein L18-3 (structural components of ribosomes) had increased amounts in samples from heat stress conditions. This agrees with previous studies on the temperature stress response, where ribosomal proteins, translation regulator factors and translation regulatory proteins played a significant role [ 39 , 64 , 65 , 66 ]. This data, combined with the fact that proteins´ abundance variations are not always correlated with changes in the corresponding transcriptome [ 67 ], can explain the lack of significant differences found in the transcription assay performed here.…”
Section: Discussionsupporting
confidence: 93%
“…The histone H4 variant TH091 and histone H2A.2.2 (core components of nucleosomes), and the 40S ribosomal protein S15a-1 and 60S ribosomal protein L18-3 (structural components of ribosomes) had increased amounts in samples from heat stress conditions. This agrees with previous studies on the temperature stress response, where ribosomal proteins, translation regulator factors and translation regulatory proteins played a significant role [ 39 , 64 , 65 , 66 ]. This data, combined with the fact that proteins´ abundance variations are not always correlated with changes in the corresponding transcriptome [ 67 ], can explain the lack of significant differences found in the transcription assay performed here.…”
Section: Discussionsupporting
confidence: 93%
“…Kinetin showed to be the most abundant cytokinin in our samples which might be related to its exogenous application in the culture media. Despite the fact that the majority of naturally occurring CKs in plants are the N 6 -isopentenyl conjugated adenine derivatives, in addition to a small amount of N 6 -aromatic CK species [64,70], exogenous addition of CKs to culture media is known to have an effect by altering and increasing the endogenous CKs pool [66,71]. Similarly, reports in Solanum tuberosum [72], Pinus pinea [73], and Pinus radiata [66] found that aromatic CKs accounted for more than 90% of the total endogenous CK pool although isoprenoid forms are generally the most abundant CKs in plant materials that have not been hormonally treated.…”
Section: Quantification Of Endogenous Cytokininsmentioning
confidence: 99%
“…The increase of proline synthesis under the influence of drying in mosses Hypnum plumaeforme Wilson and Pogonatum cirratum (Sw.) Brid. as well as its participation in cross-adaptation to low temperatures was revealed (Liu et al, 2019). Thus, analysis of the current literature data has shown that there are significant differences in the ability to accumulate proline in different moss species in the case of the same stress influence and in the same species under various types of stress, which requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The resistance of plants to stressors is determined by the functioning of constitutive and induced protective systems (Lobachevska et al, 2005;Liu et al, 2019;Hasanuzzaman et al, 2020;Oke et al, 2020).Their fundamental difference is that constitutive systems are constantly in a functionally active state and are detected immediately under short-term stress, and induced -are not normally present and are detected only in response to prolonged stress (Boots & Best, 2018;He et al, 2018;Venegas-Molina et al, 2020).…”
Section: Introductionmentioning
confidence: 99%